(untitled) (Annals of Bangladesh Agriculture, 2024)
Soil-borne diseases pose significant challenges to global potato cultivation, resulting in yield losses and economic implications. Utilizing biological control agents offers a sustainable and environmentally and friendly approach to manage these diseases. Before implementing the experiment in the field, a series of in-vitro tests were conducted to select a virulent isolate of the tested pathogens and an effective antagonistic isolate of Trichoderma harzianum. In the pathogenicity test, isolate RS-1 of Rhizoctonia solani and isolate SR-8 of Sclerotium rolfsii exhibited the highest virulence against two pathogens in potato variety ‘Cardinal’ in regard to seedling mortality (44.44-88.88%). During in vitro screening, T. harzianum isolate Tri 7 displayed the greatest ability to inhibit the mycelium growth of all tested pathogens. In the field trial, the highest seedling mortality (69.06%) was observed in T2 (Fresh seeds+ Soil inoculated with R. solani and S. rolfsii). However, the highest seedling mortality (86.94%) was reduced by treatment T7 (Fresh seeds+ Soil inoculated with R. solani and S. rolfsii +500g wheat grain colonized with Trichoderma fortified poultry compost). Treatment T7 also recorded the lowest incidences of stem canker (7.83%) and stem rot (8.64%), whereas the highest disease incidences occurred in the T2 treatment plot. Notably, treatment T7 gave the highest yield of 30.94 tons/ha, while the control plot T2 yielded the lowest at 12.17 tons/ha. Initially, Trichoderma population was minimal prior to the application of Trichoderma- fortified compost. However, populations gradually increased over time, peaking at 3 months across all treatments except the control, where no Trichoderma was applied. However, a decline in T. harzianum population was noted one month after potato harvesting. This approach offers a potential solution for managing potato soil-borne diseases in a sustainable and environmentally friendly manner. Ann. Bangladesh Agric. (2023) 27 (1): 81-92